Co-expression of citrulline-nitric oxide cycle enzymes and decreased glutamine synthetase expression in different regions of brain in epilepsy rat model - Swamy, Mummedy; Wan Yusof, Wan Roslina; Mat Zin, Intan Nurfirdaus; Sirajudeen, K. N. S.; Mustapha, Zulkarnain; Govindasamy, Chandran (Academic Journal, 2011)
The aim of this study was to determine the mRNA expression of nitric oxide synthetase (NOS), argininosuccinate synthetase (AS), argininosuccinate lyase (AL) and glutamine synthetase (GS) in different regions of brain in rats subjected to kainic acid (KA) mediated epilepsy. The short term (acute) group animals were sacrificed after 2 h and the long term (chronic) group animals were sacrificed after 5 days of single injection of KA. After decapitation of rats, cerebral cortex (CC), cerebellum (CB) and brain stem (BS) were separated and in their homogenates, the relative amount of nNOS, iNOS, AS, AL and GS mRNA was assessed by reverse transcriptase-polymerase chain reaction (RT-PCR). Results showed an increased expression of iNOS in all brain regions tested in chronic group as compared to either control or acute group, and it indicate a favorable condition of nitric oxide production. AL expression was significantly increased only in CB in acute group whereas in chronic group it is increased in CC and CB and decreased in BS as compared to control. The aforementioned increased expression of AL may contribute effective recycling of citrulline to arginine. No change in expression of nNOS and AS in both acute and chronic groups of epilepsy. GS expression was significantly decreased only in chronic group of epilepsy in all brain regions tested when compared with control group. The decreased GS may be contributing prolonged availability of glutamate in chronic epilepsy.